Peningkatan Literasi Digital dan Etika Berinternet melalui Pembelajaran PPKn: Studi PTK di SMP Negeri 13 Madiun - Ghiffari Ramadhan, Aqsal; Sukariyadi, Teja Insyaf; Widodo, Slamet (Allimna: Jurnal Pendidikan Profesi Guru, 2025)
This classroom action research aims to enhance students’ understanding and skills in digital literacy and internet ethics through the Pancasila Education subject among 8th-grade students at SMP Negeri 13 Madiun. The study employed a qualitative approach supported by quantitative data, involving 23 students using three learning cycles. Data were collected through observations, student assignments, and pretest-posttest results. The learning design integrated digital platforms such as Google Classroom, YouTube, and interactive games like Interland to support contextual digital citizenship education. Findings indicate a steady increase in students’ cognitive and practical competencies related to digital literacy and online ethics, as reflected by the rise in average pretest and post-test scores with pretest average scores at 82.43 and post-test scores reaching 86.43, accompanied by improvements in digital practice skills such as case analysis (mean: 87.3) and ethical behavior simulations (mean: 88.0). The study concludes that the use of digital-based, problem-centered learning methods is effective in promoting critical thinking, ethical awareness, and responsible online behavior. These results reinforce the importance of embedding digital literacy within civics education to prepare students for diverse and democratic digital environments.